An Analysis of Jargon Used in Political Website - Dewi Syafitri; M Ikhsan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The objectives of the study were to describe the forms, meanings, and functions of Political Jargon Which were found in Political Website. This study mainly aimed to describe the jargon used in political news of CNN politics as the Political Website. The writers used a qualitative descriptive method in classifying and analyzing the data. After investigating the forms, meanings, and functions of jargon in CNN politics on 1st -30th May, 2016, the writers found several findings. The political jargon in this website can be analyzed in forms were 53 words, 15 phrases, 5 abbreviations and there was no acronym, in the lexical meanings categories there were 58 denotative meanings and 15 connotative meanings from 73 data and the functions of Political Jargon were a belongings to a specific group, to communicate and signal for identification of political group. In conclusion, the jargon used to convey the meaning and to communicate to the readers, in this context as a signal in politics fields. So, the readers will be familiar in using some terms of political jargon in everyday speech. Keywords: Jargon, Political Website, Meaning